THE APPEARANCE OF RUSSIAN BELIEVERS IN THE CONTEXT OF RELIGIOUS IDENTITY (ONE RESEARCH CASE) - S. V. Ryazanova (Концепт: философия, религия, культура, 2018)
The research is devoted to ideas of believers’ appearance as one of the ways of religious consciousness formation. The concept of appearance includes clothes and attributes connected with the change of personal shape. The statement about a lack of exact initial ideas concerning the features of believer’s appearance acts as a starting point for the process of individual rule-making in religious community. The set of standards of appearance for the orthodox layman is defined by the rational discourse and logic of a mythogenesis. The specific content of ideas of a believer’s image is also defined by regional traditions, age and educational qualification, features of the person lifestyle. The orthodox community of Prikamye is chosen as a case for determining the tendencies to design an ideal believer image. The believers indicating their own religiosity participating in collective religious activities have been chosen as respondents. Raised issues concerned the requirements to the parishioner appearance, using of decorative means without indicating the spheres of public life the dress-code should be realized. The research has shown three groups of believers depending on their relation to questions of appearance. Conservative parishioners insist on observance of a set of norms founded on their own life experience, tradition or popular mythological ideas and patterns. Liberal group is inclined to divide religious and secular spheres, rationally proving the norms accepted by them and displacing requirements to appearance only in the situations connected with collective religious activity. Supporters of full freedom of choice in the question of appearance don’t connect the religiosity with clothes and cosmetics, linking it just to spiritual improvement. For all groups the appearance becomes not only a behavioral norm, but also a marker of participation in community, the indicator of allocation of brothers in faith, reminiscence of tradition and religious language for those who don’t know the language of canons and dogmas.